Reporting on electoral violence in Nigerian news media: "Saying it as it is"?. (December 2019) - Demarest, Leila; Langer, Arnim
Abstract: While Nigeria has a vibrant press media landscape, freedom of the press is only rated as "partly free" by Freedom House, mostly due to political influences on reporting. Yet the extent to which these influences affect the quality of reporting remains insufficiently investigated. We address this gap by analyzing how three newspapers with different political affiliations report on conflict in the run-up to the 2015 elections. Our analyses indicate that biases in reporting are generally limited, and that while political pressures are real, they are most evident in editorial choices. Résumé: Alors que le paysage médiatique au Nigéria est dynamique, la liberté de la presse n'est qualifiée que de « partiellement libre » par Freedom House, principalement en raison d'influences politiques sur les reportages. Cependant, l'impact de ces influences sur la qualité des reportages reste insuffisamment étudié. Nous comblons cette lacune en analysant la manière dont trois journaux de différentes affiliations politiques font état des conflits en préparation des élections de 2015. Nos analyses indiquent que les préjugés dans les reportages sont généralement limités et que, si les pressions politiques sont réelles, elles sont plus évidentes dans les choix éditoriaux. Resumo: Embora a imprensa nigeriana apresente uma atividade intensa, a Freedom House apenas atribuiu a classificação de "parcialmente livre" à liberdade de imprensa no país, sobretudo devido às influências políticas na atividade jornalística. Porém, continua a não existir uma investigação suficientemente profunda sobre o grau em que estas influências condicionam a qualidade jornalística. Procurando colmatar esta lacuna, debruçamo-nos aqui sobre o modo como três jornais de diferentes afiliações políticas abordaram o conflito na corrida às eleições de 2015. A nossa análise sugere que, de um modo geral, há pouco enviesamento político nas peças jornalísticas e que, apesar de serem reais, as pressões políticas se fazem sentir sobretudo nas escolhas editoriais.